1998
DOI: 10.1063/1.869550
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of flow through bead packs using the lattice Boltzmann method

Abstract: The lattice Boltzmann method (LBM) is used to simulate viscous fluid flow through a column of glass beads. The results suggest that the normalized velocity distribution is sensitive to the spatial resolution but not the details of the packing. With increasing spatial resolution, simulation results converge to a velocity distribution with a sharp peak near zero. A simple argument is presented to explain this result. Changes in the shape of the distribution as a function of flow rate are determined for low Reyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
153
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 33 publications
19
153
0
1
Order By: Relevance
“…The local counter diffusive flux, as well as the Darcy counter flow (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010), was observed in the present study (Figs. 9c, 11c).…”
Section: Negative Tail and Long Positive Tailsupporting
confidence: 54%
See 2 more Smart Citations
“…The local counter diffusive flux, as well as the Darcy counter flow (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010), was observed in the present study (Figs. 9c, 11c).…”
Section: Negative Tail and Long Positive Tailsupporting
confidence: 54%
“…(i) The local counter flow was already found for the Darcy flow (not diffusion) in porous media (Kutsovsky et al 1996;Maier et al 1998;Ogawa et al 2001;Li et al 2010). The local flux obeys the log-normal distribution for the random resistor network (de Arcangelis et al 1985) and for the Darcy flow (Cenedese and Viotti 1996;Lebon et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 also indicates self-similarity for the lowest range of Re p with a relatively flat plateau of the most probable u * x for u * x < 0.4 and then the probability of the velocity spectrum drops rather abruptly which was also observed by Maier et al (1998) and Moroni et al (2001). Johns et al (2000) who studied porous media with MRI obtained a peak for the most probable u * x at Re of about 1.…”
Section: Detailed Studies Of the Flowmentioning
confidence: 54%
“…7 also shows that there are negative u * x for all Re p . A number of studies have reported the presence of recirculation zones as well, i.e., Moroni et al (2001), Maier et al (1998), Saeger et al (1991Saeger et al ( , 1995, Lebon et al (1996), Hill et al (2001). The percentage negative u * x , which is an indication of recirculation zones, vary with Re p according to There is less recirculation within the plane 6 mm from the midplane than within the other planes probably because the overall porosity is about 20 % higher than for the other planes.…”
Section: Detailed Studies Of the Flowmentioning
confidence: 99%